THE ROLE OF THE SMOKE-FREE TASK FORCE: A STUDY OF THE SOCIAL REALITY OF SMOKE-FREE ENFORCEMENT IN THE OFFICE THE REGENT OF EAST KUTAI - Andi Didi Afriadi; Agus Sholahuddin; Sri Hartini Jatmikowati (CV. RADJA PUBLIKA, 2025)
This study analyzes the role of the Smoke-Free Area Task Force (Satgas KTR)[1] in enforcing the Smoke-Free Area policy at the East Kutai Regent's Office, using a descriptive qualitative approach[8]. The results of the study indicate that the effectiveness of the implementation of the KTR Task Force still faces significant challenges, such as individual resistance[7], limited resources, and lack of strict sanctions. Although this policy contributes to increasing collective awareness of a healthy work environment, successful implementation requires capacity building strategies, facility support, and cross-sector collaboration.